Where the wind blows: Five Star Movement's populism, direct democracy and ideological flexibility. (6th November 2017) - Manucci, Luca; Amsler, Michi
Abstract : The paper focusses on the online political discourse of the Five Star Movement (5SM) and its strategic adaptability. The main goal of the analysis is to establish how salient several topics are over time in order to test the party's ideological flexibility. Indeed, 5SM's post-ideological approach and its emphasis on direct-democratic tools might constitute a winning formula for other populist parties willing to exploit the crisis of the mainstream parties and representation. The paper, through an automated content analysis, tracks the longitudinal evolution of the salience of the topics addressed by 5SM on the party's blog. This allows us to establish which topics are at the core of the party's message and which, on the other hand, have been raised strategically over time. Results show that 5SM's discourse is very flexible and adaptable: it devotes a large space to the importance of direct democracy while flexibly addressing different topics depending on the political and social context.